Islamic Economics under Colonial Rule: The British Encounter with Muslim Northern Nigeria and Its Enduring Economic Legacies - Kabiru Uba Ibrahim; Ibrahim Dahiru Idriss; Abubakar Sadiq Uba (UIN Siber Syekh Nurjati Cirebon, 2025)
Introduction: The antagonism against Islam and Muslims, once manifested through the military campaigns of the Crusades, has evolved into more subtle yet pervasive forms in the modern era – most notably, Western imperialism and colonialism. British colonial rule in Northern Nigeria exemplifies this trajectory, as it entailed not only political domination but also efforts to impose Christian missionary ideals and systematically restructure indigenous Islamic institutions. This study investigates the historical, judicial, and economic impacts of British colonialism on Islam in Northern Nigeria, with particular attention to the responses of Muslim communities and the enduring consequences for Islamic governance and identity in the region. Methods: This paper employed historical and analytical methods, drawing on archival materials, Islamic scholarly sources, and relevant secondary literature to assess the colonial encounter. It contextualizes the arrival of Islam in Northern Nigeria and the subsequent British incursion, revealing that the most critical internal weakness of the Sokoto Caliphate was the inability of successive Sultans and Emirs to uphold the reformist ideals that defined its foundation. The dilution of Shari’a authority, particularly during the pre-independence period, led to a decline in public trust due to the appointment of poorly trained and morally compromised judicial officers. At the same time, British colonial economic policies rooted in exploitation and resource extraction undermined indigenous economic structures, marginalized Islamic leadership, and entrenched structural inequalities that continue to affect the region.Results: The research highlighted that Muslim resistance to colonial rule, often framed within the Islamic ideal of martyrdom (shahāda), played a significant role in preserving religious identity and Islamic culture. This historical resilience forms a critical basis for contemporary efforts toward Islamic institutional renewal. The paper concludes by recommending the revitalization of Islamic reformist principles, the promotion of dual (Islamic and Western) education, the restoration of integrity within Shari’a courts, the empowerment of qualified Ulama, and an economic reorientation rooted in Islamic ethics. Conclusion and Suggestion: It further suggests documenting Muslim resistance history and forging strategic partnerships with development actors to advance justice, education, and institutional strengthening within Northern Nigeria.